Pendampingan Pemasaran UMKM Somay Melalui Whatsapp Dan Baliho Sebagai Upaya Penguatan Promosi Usaha - Harjun Harjun; Abdullah Igo BD; Yuniyarti Ahiri; Abdul Rahman; Nadhine Dwi Aura Rellya; Irwan Hifu (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This study examines the application of conventional marketing and the challenges of digitalization faced by micro-scale somay (steamed fish cake) sellers in the area of the Faculty of Teacher Training and Education (FKIP), Halu Oleo University. The aim of the study is to identify marketing patterns, barriers to digital adoption, and to provide simple yet applicable solutions to improve market reach and digital payment usage. The study used a qualitative approach through direct observation and in-depth interviews with two micro-entrepreneurs: Bapak Husein, who operates from a fixed location near KOPMA, and Bapak Andi, who sells by roaming around the Masjid Muallim area. Both informants have been running their businesses for 10 and 15 years, respectively. Findings reveal that both sellers still rely predominantly on conventional marketing methods such as word-of-mouth and physical presence, while facing challenges including unstable daily income, limited promotional reach, and low digital literacy. Although both have adopted QRIS as a digital payment option, its usage remains suboptimal due to customer habits favoring cash transactions. As practical interventions, the team assisted in creating a WhatsApp customer group and designing a promotional banner (baliho) incorporating QRIS information. These low-cost digital solutions are expected to enhance business visibility, strengthen customer communication, and gradually increase digital transaction rates among micro-entrepreneurs.